Synthesis and Investigation The Biological Activity of Some New Alkenes Based on Thiazoldin-4-one Compounds - Abd Al Hassan Hamdan, Israa; J. H. Tomma (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This work has been done to prepare a series of new alkene compounds derived from 4-thiozolidinones by substituting different aldehydes, P-acetamido-phenol, and 2-mercapto-benzoimidazole, which were used as starting materials to form ester [I]a,b and then make hydrazides [II]a,b, which were used to prepare 1, 3, and 4-oxadiazoles [III]a,b, which were then used for prepared Schiff bases [IV]a-f, The next step was the synthesis of 4-thiazoldinone derivatives [V]a-f  from Schiff bases. The final step was the synthesis of alkenes [VII]a-f, the prepared derivatives were identified with spectral methods (FT-IR, 1H-NMR, mass, and CHNS). The antibacterial activity of the prepared derivatives was evaluated against four types of bacteria, positive gram (Staphylococcus aureus and Enterococcus faecalis.) and negative gram (E. coli and Pseudomonas aerugionsa). The final compounds gave high to moderate efficacy against Enterococcus faecalis bacteria, molecular modeling study against one of the SARS human coronavirus proteins was tested for synthesis compounds. Compound [VII]c had a high bonding strength with the target protein, wherever it was -8.08 Kcal/mole followed by the compound [VII]a. in the bonding strength energy, which was -7.65Kcal/mole.